Perancangan Aplikasi Silaku (Sistem Pelaporan Keuangan UMKM) Untuk Penyusunan Laporan Keuangan UMKM CV. Ambar Sari, Wonogiri Jawa Tengah - Fulan Yustinne Nadhotul Sufi'; Dinda Kharisma Putri; Sabrina Gianti; Avi Sunani (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
This research aims to help MSMEs CV. Ambar Sari in compiling financial reports automatically through theSILAKU application (MSME Financial Reporting System). CV. Ambar Sari is a company operating in the field of jellyprocessing since 1987 which continues to grow and produce until now. From all aspects of the problems faced by CV.Ambar Sari, a problem that until now has not been resolved properly is about financial management that is not inaccordance with financial accounting standards. This makes CV. Ambar Sari does not know whether the condition orcondition of the business has been running well, because this MSME only conducts simple financial records byincluding cash income and expenditure data supported by existing transaction documents. In the face of increasinglyfierce competition, CV Ambar Sari needs to adopt efficient information technology that can help improve its performance. Seeing these problems, the researchers designed the SILAKU application (MSME Financial Reporting System)based on Microsoft Excel and applied it to the process of preparing CV financial reporting. Ambar Sari agar CV. AmbarSari has financial statements that comply with financial accounting standards. The results showed that this MicrosoftExcel-based financial application can be used by CV. Ambar Sari for the preparation of financial statements so that thepreparation of financial statements can be done more easily and efficiently which is expected to be used effectively inthe long term. Within that time frame, this application will become an important tool in preparing accurate financialstatements, assisting strategic decision making, and improving the overall performance of CVAmbar Sari.